Study of the use of artificial intelligence in the tasks of building digital profiles of printing equipment - Azarenkov, Volodymyr Illich; Deineko, Zhanna (Cognum Publishing House, 2024)
Features of transformation of one color model in another on the basis of construction of ICC- profile s are analysed. Bases of profiling of devices of display, input and output of images are stated. Base concepts of the theory of artificial neural networks are described, opportunities of approximation of data by means of such networks are examined. In a practical part of work numerical modelling neural networks for approximation of the data received as a result of measurement of color targets is executed. Influence of parameters of adjustment of networks is experimentally researched at the decision of problems of smoothing of experimental data.
Keywords: color management system; profile; color look-up table; traning